OPTIMALISASI PROSES EKSTRAKSI MINYAK BIJI NYAMPLUNG MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (RSM) - Ahmad Moh. Nur; Hairul Huda; Rif'an Fathoni (Jurnal Chemurgy, 2022)
Nyamplung (Calophyllum inophyllum L.) is a plant with great potential as a fuel source that can be developed in Indonesia. The oil content of nyamplung seeds is 60-75%. This study aims to optimize the process of extracting oil from nyamplung seeds using hexane solvent at various operating conditions and obtain optimum extraction operating conditions. In the process stage, extraction will be carried out using hexane solvent with several operating variations, namely extraction temperature (35-45oC); extraction time (4-6 hours); stirring speed (200-600 rpm), the process of optimizing oil extraction from nyamplung seeds was carried out using the Response Surface Methodology (RSM). The oil obtained was then characterized through several analyzes, namely yield, acid number, density and viscosity. Based on the research results, optimization of the nyamplung seed oil extraction process resulted in an oil yield of 52.43% which was obtained at 40oC, 5 hours of extraction time and 500 rpm of stirrer speed. Optimization with the aim of maximizing the oil yield response was obtained 55.33% yield at 45oC, 6 hours extraction time and 600 rpm stirrer speed. Optimization of each oil quality does not produce a significant model response. The quality of the oil resulting from the optimization of the yield is an acid number of 10.51 mgKOH/g, a density of 0.94 g/ml, and a viscosity of 4.47 cP.Keywords: calophyllum, oil, optimization, response surface methodology